17‐β‐Estradiol increases macrophage activity through activation of the G‐protein‐coupled estrogen receptor and improves the response of female mice to Cryptococcus gattii. (20th February 2020) - Costa, Marliete C.; de Barros Fernandes, Heliana; Gonçalves, Gleisy K. N.; Santos, Anderson P. N.; Ferreira, Gabriella F.; de Freitas, Gustavo J. C.; do Carmo, Paulo H. F.; Hubner, Jôsy; Emídio, Elúzia C. P.; Santos, Julliana R. A.; dos Santos, Jane L.; dos Reis, Adelina M.; et al.
Abstract: Cryptococcus gattii (Cg) is one of the agents of cryptococcosis, a severe systemic mycosis with a higher prevalence in men than women, but the influence of the female sex hormone, 17‐β‐estradiol (E2), on cryptococcosis remains unclear. Our study shows that female mice presented delayed mortality, increased neutrophil recruitment in bronchoalveolar lavage fluid, and reduced fungal load after 24 hr of infection compared to male and ovariectomised female mice (OVX). E2 replacement restored OVX female survival. Female macrophages have more efficient fungicidal activity, which was increased by E2 and reversed by the antagonist of G‐protein‐coupled oestrogen receptor (GPER), which negatively modulates PI3K activation. Furthermore, E2 induces a reduction in Cg cell diameter, cell charge, and antioxidant peroxidase activity. In conclusion, female mice present improved control of Cg infection, and GPER is important for E2 modulation of the female response.